Relationship Between Peer Pressure And Students' Self Esteem At State Senior High School 3 Bukittinggi - Laswita, Elsa Yutri; Hartati, Sri; Afrida, Yeni; Arjoni, Arjoni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
ABSTRAK. This studys examinnes the relationsip between peer pressuere and self-esteem in grade XI students at SMA Negeri 3 Bukittinggi. Peer pressure is defined as social pressure from peer groups that encourages individuals to think and act according to group standards in order to be accepted. Whil eself-esteem referhs to an individuals appreciation of themselves, which is formed from the accumulation of experiences, thoughts, feelings, and sensations throug hout life. Self-esteem acts as a foundation for positive development in social relation ships, learning processes, creativity, and personal responsibility. This study uses a quantitative approach with a correlation method. The population involved 76 grade XI students (F1-F9) at SMA Negeri 3 Bukittinggi, with sampling using the Proportional technique of random sampling. A Likert-scale questionnaire was the tool utilised. To test the hypothesis, a correlation test was used to analyse the data. As evidenced by the acceptantce of the alternative ehypothesits (Ha) and the rejectsion of the null hypothesis (Ho), the study's findings demonstrated a strong relationship between the variables peer presseure (X) and self-esteem (Y). While other factors influence the remaining 20%, the correlation value of 80% indicates a robust associatiosn betweens peer presasure and self-esteem. Considering these findings, it can be said that there is a strong correlation between peer pressure and self-esteem in students.Kata kunci: Peer Preasure, Self Esteem, Students